A Preliminary Investigation on Smokeless Tobacco Use and Its Cognitive Effects Among Athletes - Zandonai, Thomas; Chiamulera, Cristiano; Mancabelli, Alberto; Falconieri, Danilo; Diana, Marco (Frontiers in Pharmacology, 2018)
Introduction Among athletes, an increasing use of nicotine via smokeless tobacco has been reported. However, there are currently unanswered questions about whether the use by athletes is due to nicotine’s addictive properties and/or to benefits in physical and cognitive performance (e.g., decision-making). In this original article we reported about, i), snus-induced reinforcing effects among snus-user athletes (Survey) and, ii), the effects of snus on the Iowa Gambling Task (IGT) in snus-user skiers (Experimental study). IGT is an experimental neuropsychological task that has been previously used on athletes and addicts to test decision-making. Methods Survey: data were collected with the modified Cigarette Evaluation Questionnaire (mCEQ) that was administered to 61 winter sport athlete snus-users in Northern Italy. Experimental study: IGT data included: amount of money earned, number of choices from advantageous and disadvantageous decks and overall net score. Eighteen male snus-users were tested under satiety or after 12-hour abstinence conditions according to a crossover design. Results Survey: the comparison between occasional vs. regular snus-users showed a statistically significant difference in satisfaction (P=0.0088), calm (P=0.0252) and enjoyment (P=0.0001) mCEQ items suggesting a snus intake/effect relationship. Experimental study: significantly higher IGT net scores were found during the first 20 choice cards after abstinence vs. satiety conditions (P=0.0024). Conclusions In the Survey, regular snus use induces greater satisfaction and psychological reward than occasional use. In the Experimental study, snus intake might produce an early and transient cognitive improvement on IGT in abstinent snus-users, presumably acting as a withdrawal relief.